Designing a Restitution Experiment Using Smartphone Sound Sensor - Najmi Hiyan Fathinah; Asep Akmal Fadia Nurhalim; Rahma Alliya Aqquilla; Ika Mustika Sari; Alfiansyah Sandion Prakoso; Rizki Zakwandi (Universitas Nurul Huda, 2025)
This study explores the efficiency level of two experimental methods for determining the coefficient of restitution, which have been widely conducted in previous research. Using smartphones as tools in physics experiments, the coefficient of restitution can be determined through visual analysis (camera) and sound sensors to detect collisions. Phyphox is used to record time intervals and the height of the ball after impact based on the sound of the collision with the floor. Additionally, Tracker is employed for visual motion analysis of the object during the collision. The coefficient of restitution calculated using Phyphox yielded a value of 0.894 ± 0.017, while Tracker provided a value of 0.888 ± 0.014. The results indicate by reviewing the percentage error between the two methods (0.715%), Phyphox and Tracker can provide accurate data for determining the coefficient of restitution, making them effective and efficient physics experiment-based learning tools in schools.